The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1469-0691.2007.01744.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of one-tube multiplex PCR, automated ribotyping and intergenic spacer (ITS) sequencing for rapid identification of Acinetobacter baumannii

Abstract: Acinetobacter baumannii has emerged as a serious cause of nosocomial infections. Rapid identification of this pathogen is required so that appropriate therapy can be given and outbreaks controlled. This study evaluated a multiplex PCR and an automated ribotyping system for the rapid identification of Acinetobacter baumannii. In total, 22 different reference strains and 138 clinical isolates of Acinetobacter spp., identified by 16S-23S rRNA intergenic spacer (ITS) sequence analysis, were evaluated. All A. bauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(116 citation statements)
references
References 30 publications
1
110
0
1
Order By: Relevance
“…After 48 hours, the culture of the vitreous humor revealed the presence of the antibiotic resistant A. baumannii bacteria through automation identification in VITEK 2 compact AST 281, confirmed by molecular biology (Fig. 1) through species-specific primers that amplify a fragment of 208 base pairs of the internal transcribed spacer (ITS) of A. baumannii ribosomal DNA, by the DNA polymerase chain reaction (PCR) (Chen et al, 2007). On day 15(POD), the patient developed lancinating pain, worsening of the ocular condition, loss of light perception, and no response to previous treatments.…”
Section: Case Reportmentioning
confidence: 98%
“…After 48 hours, the culture of the vitreous humor revealed the presence of the antibiotic resistant A. baumannii bacteria through automation identification in VITEK 2 compact AST 281, confirmed by molecular biology (Fig. 1) through species-specific primers that amplify a fragment of 208 base pairs of the internal transcribed spacer (ITS) of A. baumannii ribosomal DNA, by the DNA polymerase chain reaction (PCR) (Chen et al, 2007). On day 15(POD), the patient developed lancinating pain, worsening of the ocular condition, loss of light perception, and no response to previous treatments.…”
Section: Case Reportmentioning
confidence: 98%
“…Species from Acinetobacter can be easily differentiated. However, this method is less discriminatory than the PFGE method [19]. Therefore at present, ribotyping has been replaced by the PFGE method.…”
Section: Ribotypingmentioning
confidence: 99%
“…The results confirmed that all strains were A. baumannii. The primer sequences used for the 16S-23S rDNA A. baumannii-specific PCR amplification were P1: 5'-CATTATCA CGGTAATTAGTG-3' and P2: 5'-AGAGCACTGTGCACTTAAG-3' (Chen et al, 2007). A genetic testing kit was provided by the Wuxi Institute of Cloning Genetic Technologies (Wuxi, China).…”
Section: Strain Source Strain Molecular Identification and Drug Susmentioning
confidence: 99%